Preliminary Psychometric Properties of the Chinese Version of the Work-Related Quality of Life Scale-2 in the Nursing Profession - Shike Lin; Naesinee Chaiear; Jiraporn Khiewyoo; Bin Wu; Nutjaree Pratheepawanit Johns (Elsevier, 2013)
Objectives: As quality of work-life (QWL) among nurses affects both patient care and institutional standards, assessment regarding QWL for the profession is important. Work-related Quality of Life Scale (WRQOLS) is a reliable QWL assessment tool for the nursing profession. To develop a Chinese version of the WRQOLS-2 and to examine its psychometric properties as an instrument to assess QWL for the nursing profession in China. Methods: Forward and back translating procedures were used to develop the Chinese version of WRQOLS-2. Six nursing experts participated in content validity evaluation and 352 registered nurses (RNs) participated in the tests. After a two-week interval, 70 of the RNs were retested. Structural validity was examined by principal components analysis and the Cronbach's alphas calculated. The respective independent sample t-test and intra-class correlation coefficient were used to analyze known-group validity and test-retest reliability. Results: One item was rephrased for adaptation to Chinese organizational cultures. The content validity index of the scale was 0.98. Principal components analysis resulted in a seven-factor model, accounting for 62% of total variance, with Cronbach's alphas for subscales ranging from 0.71 to 0.88. Known-group validity was established in the assessment results of the participants in permanent employment vs. contract employment (t = 2.895, p < 0.01). Good test-retest reliability was observed (r = 0.88, p < 0.01). Conclusion: The translated Chinese version of the WRQOLS-2 has sufficient validity and reliability so that it can be used to evaluate the QWL among nurses in mainland China.